Surface dimple machining in whirling. (October 2015) - Matsumura, Takashi; Serizawa, Masaki; Ogawa, Tomohiro; Sasaki, Masanori
Highlights: A machining of dimple surfaces in whirling is presented for functional surfaces. The dimples are formed with controlling the speeds of tool and workpiece. The dimple surfaces are machined on cylinders at high production rates. A mechanistic model is presented to control the dimple shape. The forming process of the dimple is simulated with time. Abstract: Structured dimples on product surfaces are required for control of the surface functions such as friction. The dimple machining, therefore, should be performed in large surface areas at high machining rates. This study presents a novel machining to fabricate the dimples on the cylinder surfaces in whirling, which originally machines threads such as ball screws with rotating the workpiece and the tool mounted on a whirling ring. In the presented machining, the circumferential speeds of the workpiece and the tool are controlled so that the tool edge indents on the cylinder surface without cutting in the dimple machining. The configuration in the machining are discussed to characterize the indentation process. A mechanistic model in the dimple machining, then, is presented to control the dimple shapes. The time-series analysis in the indentation process is performed to simulate the dimples for the machining parameters. Some machining examples are shown to verify the high speed dimple machining.